Penguatan Karakter Siswa melalui Pengintegrasian Modal Sosial dalam Pembelajaran IPS - Muzakir (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2023)
Social capital really needs to be developed in education, especially in the learning process in order to strengthen student character. Having strong social capital in students is a reflection of the results of learning outcomes, especially in social studies learning. This study aims to provide knowledge about the integration of social capital in social studies learning to strengthen student character. Social capital that is integrated into social studies learning includes: 1) elements of social capital consisting of participation in a network, reciprocity, trust, social norms, values ​​and proactive actions; 2) values ​​in social capital which include Universalism, Benevolence, Tradition, Conformity and security. The method used in this study is to analyze literature on topics related to books, journals and other relevant sources obtained from various sources both offline and online. The results of the study show that the elements of social capital are participation in a network, reciprocity, trust, social norms, values ​​and proactive actions; and values ​​in social capital which include Universalism, Benevolence, Tradition, Conformity and security are very possible to be integrated into social studies learning both in the process, learning material (content) and in learning assessment to strengthen student character.